Risk for Cesarean section in women of advanced maternal age under the changed reproductive policy in China: A cohort study in a tertiary hospital in southwestern China. Issue 9 (1st July 2019) - Xie, Min; Lao, Terence T; Du, Mingyu; Sun, Qian; Qu, Zaiqing; Ma, Junnan; Song, Xinyan; Wang, Mingfang; Xu, Dongqiong; Ma, Runmei
Abstract: Aim: To describe changed epidemiological features of advanced maternal age (AMA) and to examine the effect of AMA on the risk for Cesarean section (CS) in a Chinese pregnant population. Methods: This retrospective single‐center cohort study investigated the changes of epidemiological features of AMA parturients with respect to the revised reproductive policy in China in 43 702 singleton deliveries with live birth at ≥28 weeks managed from January 2005 to December 2016. We also evaluated the pregnancy outcomes in different age groups and risk factors of CS with multivariate analysis. Results: In this 12‐year study period, the average maternal age increased from 28.5 to 30.2 years, and the proportion of AMA raised from 6.5% to 17.2%. AMA was significantly associated with increased risk of adverse pregnancy outcomes, and after adjustment for confounding factors, AMA remained a significant independent risk factor for CS. Furthermore, the effect of AMA in nulliparous women on the risk of CS was more significant than in multiparous women, while the history of previous CS (adjusted odds ratio 39.85) and interdelivery interval ≥10 years (adjusted odds ratio 1.52) also increased the risk of CS in multiparous women. Conclusion: AMA increased the risk of a number of adverse pregnancy outcomes, and was independently associated with increased risk for CS. The increasing number of AMA parturients with risk factors is likely to increase CS rate in China in the near future, thus it is imperative to reduce the rate of primary CS as a matter of policy.